Evaluación del impacto de las políticas públicas del buen vivir en organizaciones agroproductivas solidarias de los cantones Junín, Montecristi y Olmedo - Espinoza Mera, Yeroly Carolina (2019)
The objective of this research was to evaluate the impact of public policies of Good Living in the Solidarity agroproductive organizations in the Junín, Montecristi and Olmedo cities, this was executed through the successive methodological phases, mainly within the research was considered to determine theoretical concepts to base the impact of public policies of Good Living, to later select or set the evaluation indicators the same ones that were carried out in the investigation, allowing the evaluation of the public policies of Good Living to the solidarity agroproductive organizations. However, it should be noted that in Montecristi the evaluation could not be carried out because there was little access to information to go to the places or addresses that the SEPS (Superintendence of Popular and Solidarity Companies) had established. In addition, this canton contains water scarcity, air and soil pollution since these factors are of vital importance for the daily work of farmers. It is transcendental to highlight that the associates contributed to help with the research and at the same time to manifest about the public policies, based on the obtained data it was observed that in the treatment sample the associates have received support from the Government for the development of their productive activities and finally, through the results achieved it was determined that some public policies had effective applicability represented by 68%, while others reached a partial applicability reflected in 34% and others that had an inefficient applicability with a 0 %.